Optimal damper location for mid-high frequency vibration control on built-up structures: case study using VA one - Abdul Muthalif, Asan Gani (Trans Tech Publications Ltd., Switzerland, 2012)
This paper presents a guide to identify optimal damper location to reduce vibration on built-up structures. The guide is derived from simulation studies carried out on a set of benchmark models. Optimization is carried out using genetic algorithm. Optimal location is found using found using Generic algorithm and the hybrid method. The hybrid modelling method combines the finite element method (FEM) and Statistical energy analysis (SEA) to provide an efficient response predication for mid-high frequencies. The guide to find optimal damper location is tested on a fuselage model of Boeing 737. The fuselage model is developed using VA One software. Good agreement is seen for the optimal locations using the simple guide and result from VA One